Environmental potential applications of alkali metal exchanged zeolite x in carbon dioxide adsorption - Joshi, U. D.; Joshi, P. N.; Roh, H. S.; Yoon, W. L.; Shiralkar, V. P. (Research Journal of Chemistry and Environment, 2011)
The increasing atmospheric CO2 concentration, mainly caused by the Thermal Power Stations, Industrial sector and fossil fuel combustion, has led to consequences of global warming. Zeolitic adsorption processes is more promising, energy saving and viable method for CO2 removal in Comparison to other technologies. In order to examine the behavior and to establish the trends in carbon dioxide sorption, NaX zeolite (Si/Al = 1.15) and it's the modified forms with identical degree (55.5 +/- 2.5) of exchange by K+, Rb+ and Cs+ cations have been selected., The samples were characterized by powder XRD, Low temperature nitrogen adsorption/desorption measurements, chemical analysis and also for the intermediate electronegativity and the partial charges on the atoms using Sanderson's electronegativity equalization principle. The isotherms of carbon dioxide using these NaX, NaKX, NaRbX and NaCsX samples were measured at an interval of 30 K in the temperature range of 273 to 363 K up to 600 Torr. The uptake of CO2 was found to depend on both, the size of the nonframework cation and the temperature at which the isotherms were measured. The cations with lower charge density will have lower extent of electrostatic interaction with the sorbate molecules. Since CO2 has more linear quadrupole moment, it interacts mainly with the extra-framework cations and framework oxygen. The carbon dioxide sorption data satisfactorily represented by Langmuir and also analyzed for the chemical affinity. The Isosteric heat (q(st)) of NaX for the coverage of 20 molecules per unit cell is nearly equal to 26 kJ, mol(-1). The NaX and NaKX comparatively show a flat heat profile with the increasing amount sorbed than those of NaRbX and NaCsX indicating a balance between the strength of energetic heterogeneity of sorbate-sorbent interactions and sorbate-sorbate interactions.
Keywords: CO2 sorption; Ionic exchange; Isosteric heat; NaX zeolite; Theoretical models